INCREASING STUDENTS’ WRITING SKILL TO DEVELOP IDEAS IN DESCRIPTIVE TEXT THROUGH THE USE OF INTERNET-BASED MATERIALS - Aulia Hanifah Qomar (Premise: Journal of English Education and Applied Linguistics, 2014)
The objective of the research are: (1) to identify weather and to what extend the use of internet-based materials increase students’ skill in developing ideas to write descriptive text; and (2) to describe the strengths and the weaknesses of internet-based materials in this research. The Classroom Action Research which was carried out at Muhammadiyah University of Metro for the third semester in the academic year of 2012/2013. In collecting the data, she used interviews, observations, questionnaires, diaries, documents, and tests. The data were analyzed through Constant Comparative Method and descriptive statistics. The research findings showed that internet-based materials can increase students’ writing skill in developing ideas to write descriptive text. The increase in students’ writing skill includes: 1) The number of appropriate paragraphs in describing something is all describing the topic. 2) The number of appropriate sentences in describing something was all representing main idea in the paragraphs. 3) Students had knowledge able substantive, development of thesis topic relevant to assign topic. 4) Students were fluent expression, ideas clearly stated / support, well organized, logical sequencing, cohesive and correct the generic structure of descriptive text such as identification and description. 5) Students were sophisticated range, effective word or diction choice and usage word from mastery, appropriate register. 6) Students have effective complex construction, few errors of agreement, tense number, word order/function, articles, pronoun, and preposition. 7) Students were demonstrated mastery of conventions, few errors spelling, punctuation, capitalization, paragraphing. The final result of the tests showed that their score were increasing in the mean score; from 69 (pre test) to 73 (test in cycle 1), 79 (test in cycle 2), and 81 (in cycle 3). It was above the minimum standard of the school (72). Related to the strengths of internet-based materials, includes: 1) Teaching and learning were more effective; 2) The students were interested in the lesson especially in writing; 3) The students’ writing ideas were well developed; 4) The students did the task given by the lecturer; 5) The students’ knowledge was improved. The weaknesses of internet-based materials includes: 1) The students were not controlled when they used internet; 2) The students frequently opened another sites for teaching and learning process; 3) Students needed a long time to access the materials from the internet; 4) The time management related to the classroom situation; 5) Teaching and learning process became crowded.